2017
DOI: 10.1056/nejmoa1604267
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Magnetic Resonance Imaging in Patients with Cardiac Devices

Abstract: BACKGROUND Patients who have pacemakers or defibrillators are often denied the opportunity to undergo magnetic resonance imaging (MRI) because of safety concerns, unless the devices meet certain criteria specified by the Food and Drug Administration (termed “MRI-conditional” devices). METHODS We performed a prospective, nonrandomized study to assess the safety of MRI at a magnetic field strength of 1.5 Tesla in 1509 patients who had a pacemaker (58%) or an implantable cardioverter–defibrillator (42%) that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
143
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 264 publications
(165 citation statements)
references
References 45 publications
11
143
0
11
Order By: Relevance
“…Two large prospective registries, MagnaSafe and Nazarian et al, 41 established the safety of 1.5 Tesla MRI in 3009 patients with non-MRI conditional devices. 42 Both studies used similar protocols, with the notable exception of exclusion of ICD patients who are pacemaker dependent and those undergoing thoracic MRI in the MagnaSafe study.…”
Section: Mri In Patients With Cardiac Implantable Electronic Devicementioning
confidence: 99%
“…Two large prospective registries, MagnaSafe and Nazarian et al, 41 established the safety of 1.5 Tesla MRI in 3009 patients with non-MRI conditional devices. 42 Both studies used similar protocols, with the notable exception of exclusion of ICD patients who are pacemaker dependent and those undergoing thoracic MRI in the MagnaSafe study.…”
Section: Mri In Patients With Cardiac Implantable Electronic Devicementioning
confidence: 99%
“…Limitations in the use of MRI are a long acquisition time and incompatibility with metallic implants such as pacemakers. The latter concern, however, seems to be overestimated based on most recent literature [53]. In most clinics, MRI availability is also a limiting factor compared with CT.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…3,4 However, there have been major concerns that those scans might interact with and cause malfunction of the CIEDs or permanent damage to the device, leads, or heart at the lead-tissue interface. 5 Because there were early reports implicating MRI scans in the death of several patients with implanted devices, [6][7][8][9] it has been considered that MRI is contraindicated in patients with a CIED.…”
mentioning
confidence: 99%
“…Most recent studies have reported no long-term clinically significant adverse events in patients with non-MRI-conditional CIEDs that underwent thoracic and non-thoracic MRI exams. 4,10 On the other hand, MRI-conditional CIEDs have been developed to extend an MRI indication to patients with CIEDs, and currently are clinically available. Several studies have proved the safety of MRI scans in patients with the MRI-conditional CIEDs.…”
mentioning
confidence: 99%